2022
DOI: 10.1039/d2cc02497g
|View full text |Cite
|
Sign up to set email alerts
|

A redox-switchable catalyst with an ‘unplugged’ redox tag

Abstract: Two bis-(propyl-imidazolium)-napthalenediimide (NDI) salts were prepared and used as N-Heterocyclic carbene (NHC) precursors for the preparation of dimetallic complexes of rhodium and iridium. Infrared spectroelectrochemical studies indicate that the metals...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

6
0

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 33 publications
3
5
0
Order By: Relevance
“…The reaction was carried out in CD 3 CN at 80 °C, and the evolution of the process was monitored by 1 H NMR spectroscopy. As can be observed from the time‐dependent reaction profile shown in Figure 6a, the reaction exhibits a zeroth order dependence on the substrate, in accordance with previous studies, [12a,c,18] and under these reaction conditions the reaction rate is 1.18±0.04×10 −5 Ms −1 . Then the reaction was repeated under the same conditions, but with the addition of coronene or TBAF.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…The reaction was carried out in CD 3 CN at 80 °C, and the evolution of the process was monitored by 1 H NMR spectroscopy. As can be observed from the time‐dependent reaction profile shown in Figure 6a, the reaction exhibits a zeroth order dependence on the substrate, in accordance with previous studies, [12a,c,18] and under these reaction conditions the reaction rate is 1.18±0.04×10 −5 Ms −1 . Then the reaction was repeated under the same conditions, but with the addition of coronene or TBAF.…”
Section: Resultssupporting
confidence: 90%
“…In order to address this point, we decided to study the catalytic activity of 2 in the cycloisomerization of alkynoic acids as a model catalytic reaction. We find this reaction suitable for the study, because it is an easy NMR‐monitorable reaction, and because in previous studies we found this reaction is very sensitive to changes in the electron‐donating properties of the ligands and, therefore, particularly useful for carrying out studies on redox‐switchable [12a,c] and supramolecularly modified [8] catalysts. We first studied the cycloisomerization of 4‐pentynoic acid in the presence of 1 mol % of complex 2 .…”
Section: Resultsmentioning
confidence: 99%
“…The resulting reaction profiles are shown in Figure 4. As can be observed from the plots, the reactions follow a zeroth order dependence on the substrate, in agreement with previous studies [8c,d,23] . This zeroth order dependence of the reaction rate on the substrate concentration means that the resting state the substrate is already coordinated to the catalyst through the alkyne.…”
Section: Methodssupporting
confidence: 91%
“…As can be observed in the plots shown in Figure 4, the addition of coronene produces a significant improvement in the catalytic activity, which is manifested by a 2.7‐fold increase of the reaction rate. It is also important to point out that this enhancement on the activity of the catalyst for this specific reaction is similar to that obtained using rhodium complexes with redox‐switchable ligands, [8c,d] thus indicating that the supramolecular control of the process can compete in magnitude with the control provided by redox‐switchable catalysts. Again, when we performed the reaction in the presence of pyrene, instead of coronene, no improvement in the reaction rate was observed, as a consequence of the negligible interaction between pyrene and complex 1 (Figure S26).…”
Section: Methodssupporting
confidence: 71%
“…We recently became interested in the use of NDI and PDI functionalities for the preparation of NHC-based redox-switchable catalysts. The presence of the NDI or PDI moieties appended to the NHC ligands allowed toggling the properties of the metals between three electronic levels, and this was used for exploring the redox-switchable properties of the catalysts in the cycloisomerization of alkynoic acids, the hydroamination of alkynes, and the [3+2] cycloaddition of diphenylcyclopropenone and acetylenes . In the incorporation of the NDI moieties into the NHC ligand, we used two strategies, which included the fusion of the NHC ligand at the core positions of the NDI moiety ,, or the functionalization of the NDI at the imide positions .…”
Section: Introductionmentioning
confidence: 99%